2021
DOI: 10.1371/journal.pone.0244685
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence of C4 plant consumption in mound building Macrotermes termites from savanna woodland chimpanzee sites

Abstract: Stable isotope analysis is an increasingly used molecular tool to reconstruct the diet and ecology of elusive primates such as unhabituated chimpanzees. The consumption of C4 plant feeding termites by chimpanzees may partly explain the relatively high carbon isotope values reported for some chimpanzee communities. However, the modest availability of termite isotope data as well as the diversity and cryptic ecology of termites potentially consumed by chimpanzees obscures our ability to assess the plausibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…The relatively low abundance of the Chequered Elephantshrew on Macrotermes mounds is surprising, given that elephant shrews broadly (Woodall and Currie, 1989) and this species specifically (Redford, 1987) is known to feed on termites. It could be that the larger size of M. subhyalinus and M. bellicosus are chemically or anatomically prohibitive to consume (Longhurst et al, 1978;Phillips et al, 2021). Our interpretation is that this could reflect a behavioral strategy to avoid the other mesomammals attracted to termite mounds.…”
Section: Discussionmentioning
confidence: 79%
“…The relatively low abundance of the Chequered Elephantshrew on Macrotermes mounds is surprising, given that elephant shrews broadly (Woodall and Currie, 1989) and this species specifically (Redford, 1987) is known to feed on termites. It could be that the larger size of M. subhyalinus and M. bellicosus are chemically or anatomically prohibitive to consume (Longhurst et al, 1978;Phillips et al, 2021). Our interpretation is that this could reflect a behavioral strategy to avoid the other mesomammals attracted to termite mounds.…”
Section: Discussionmentioning
confidence: 79%
“…Macrotermes mounds are abundant in both miombo and riverine forests throughout the site. Thirteen of the fourteen colonies of the species M. subhyalinus in this study were taxonomically identified by SP with support by Rudolf Scheffrahn at Fort Lauderdale Research & Education Center (Phillips et al, 2021).…”
Section: Study Sitementioning
confidence: 99%
“…Moisture hastens the development of alates in some species, and the timing of flights based on rain accumulation may synchronize with the most productive time for workers in young colonies to forage for food (Sands, 1965;Nutting, 1969). Perhaps ~200 mm of rainfall in the Issa Valley is the best time for nuptial pairing of alates to connect, reproduce, and build colonies in time for workers to forage when vegetative resources that Macrotermes prefer at Issa are most abundant (Phillips et al, 2021). That dispersal flights peak in a similar range of cumulative rainfall to the ability of researchers to successfully extract termites from flight holes further links chimpanzee termite-fishing ability to Macrotermes reproductive ecology.…”
Section: Alate Dispersal Flightsmentioning
confidence: 99%
“…Previous studies on dietary composition of fungus‐growing termites (Boutton et al, 1983; Lepage, 1979; Phillips et al, 2021) have often focused on the relative proportions of plant matter from woody plants (C3 plants) and grasses (C4 plants), as in tropical environments these two plant groups commonly have distinctive and nonoverlapping C isotope compositions due to their different photosynthetic pathways (O'Leary, 1988; Tieszen et al, 1979). In Kenya, Macrotermes michaelseni is believed to mainly forage on grass (Lepage, 1979, 1981a, 1981b; but see Boutton et al, 1983), whereas in western Tanzania, the closely related Macrotermes subhyalinus was found to mostly consume woody plant litter (Phillips et al, 2021). The West African Macrotermes bellicosus and the oriental Macrotermes carbonarius seem to also mainly feed on leaf and wood litter of deciduous trees (Collins, 1981a; Matsumoto & Abe, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon and nitrogen stable isotopes are commonly used for dietary assessments as their composition in animal tissues (DeNiro & Epstein, 1978, 1981) or fungal mycelia (Gleixner et al, 1993; Hobbie et al, 1999; Kohzu et al, 1999) closely resembles that of the utilized food or substrate. Previous studies on dietary composition of fungus‐growing termites (Boutton et al, 1983; Lepage, 1979; Phillips et al, 2021) have often focused on the relative proportions of plant matter from woody plants (C3 plants) and grasses (C4 plants), as in tropical environments these two plant groups commonly have distinctive and nonoverlapping C isotope compositions due to their different photosynthetic pathways (O'Leary, 1988; Tieszen et al, 1979). In Kenya, Macrotermes michaelseni is believed to mainly forage on grass (Lepage, 1979, 1981a, 1981b; but see Boutton et al, 1983), whereas in western Tanzania, the closely related Macrotermes subhyalinus was found to mostly consume woody plant litter (Phillips et al, 2021).…”
Section: Introductionmentioning
confidence: 99%